2014
DOI: 10.1007/s12032-014-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of c2orf68 and PI3K/Akt/mTOR pathway in human colorectal cancer

Abstract: The aim of the research is to determine whether c2orf68 gene plays a role in the carcinogenesis of human colorectal cancer and to study the function of c2orf68 belonging to the UPF0561 family. The mRNA expression levels of c2orf68 were examined in 30 pairs of human colorectal adenocarcinoma tissues and adjacent normal colorectal tissues by qRT-PCR. The SW480 and SW620 cell lines were transfected with siRNA against the c2orf68 gene and set gene. The expressed mRNA levels of Akt, PI3K, Bax, Bcl-2, caspase3, c-My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…Our study revealed that cell apoptosis increased, cell proliferation and cell migration decreased when c2orf68 was inhibited in SW480 cells. These results are consistent with our previous study (16). In addition, we also demonstrated that cell apoptosis increased while cell proliferation and cell migration decreased in SW480 -HuR and SW480 -c2orf68,-HuR cells.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study revealed that cell apoptosis increased, cell proliferation and cell migration decreased when c2orf68 was inhibited in SW480 cells. These results are consistent with our previous study (16). In addition, we also demonstrated that cell apoptosis increased while cell proliferation and cell migration decreased in SW480 -HuR and SW480 -c2orf68,-HuR cells.…”
Section: Discussionsupporting
confidence: 93%
“…The cell apoptosis rate, cell proliferation and cell migration in SW480 -c2orf68,-HuR cells which has more significant results than that in SW480 -HuR cells revealed that c2orf68 and HuR may have a synergistic effect in regulating cell apoptosis, cell proliferation and cell migration. This study differed from our previous study (16), which focused on the PI3K/Akt/mTOR signaling pathway and its downstream molecules, such as Akt, PI3K, Bcl-2, c-Myc, cyclin D1 and bax when c2orf68 was inhibited. A recent study showed that the HuR expression level is closely related to AKT phosphorylation and PI3K/AKT/NF-κB signaling can notably elevate HuR gene transcription (18).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The use of specific siRNAs to block or inhibit the activity of a gene is a well-established methodology for in vitro models, particularly to investigate gene function [ 57 59 ]. However, the use of siRNAs as therapeutic agents in tumor models has not been entirely successful, especially for invasive or metastatic cancers [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%